2017
DOI: 10.1016/j.jeem.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Household electrification and indoor air pollution

Abstract: published by Elsevier. It is posted here by agreement between them. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(76 citation statements)
references
References 46 publications
1
75
0
Order By: Relevance
“…Such an exercise is particularly costly, but it is extremely useful if one wants to minimize measurement error and self-reporting bias. Useful examples for objective IAP measures, ICS usage monitoring and morbidity assessments are provided in Barron and Torero (2016), Ruiz-Marcado et al (2011) and Beltramo and Levine (2013), Hanna et al (2016). This may induce the development of innovative financing mechanisms, for example through carbon and impact finance (Simon et al 2014).…”
Section: Time Allocation Fuel Use and Expendituresmentioning
confidence: 99%
“…Such an exercise is particularly costly, but it is extremely useful if one wants to minimize measurement error and self-reporting bias. Useful examples for objective IAP measures, ICS usage monitoring and morbidity assessments are provided in Barron and Torero (2016), Ruiz-Marcado et al (2011) and Beltramo and Levine (2013), Hanna et al (2016). This may induce the development of innovative financing mechanisms, for example through carbon and impact finance (Simon et al 2014).…”
Section: Time Allocation Fuel Use and Expendituresmentioning
confidence: 99%
“…Studies have found effects of access to electrification on a wealth of socioeconomic variables like employment (Dinkelman, 2011), indoor air quality (Barron and Torero, 2015a), energy use, time allocation, and income (Barron and Torero, 2015b;Bensch, Kluve, and Peters, 2010;Khandker, Barnes, andSamad, 2012, 2013;Chakravorty, Pelli, and Marchand, 2013), housing value and human development (Lipscomb, Mobarak, and Barham, 2013). However, there is still scarce evidence on the role that access to electricity plays on firm performance and industry development, two key elements of economic growth.…”
Section: Manuel Barronmentioning
confidence: 99%
“…Measurements of indoor PM 2.5 concentrations in kerosene‐using homes support modeled estimates and are also suggestive of a potential benefit of kerosene use elimination. Kerosene‐using homes that received electricity connections in El Salvador experienced a 66% reduction in living room PM 2.5 concentrations during peak lighting hours . Repeated PM 2.5 measurements in the living rooms of Ugandan households showed that concentrations in homes with solar lamps were about 40% of those in households using simple wick lamps .…”
Section: Introductionmentioning
confidence: 99%
“…Kerosene-using homes that received electricity connections in El Salvador experienced a 66% reduction in living room PM 2.5 concentrations during peak lighting hours. 16 Repeated PM 2.5 measurements in the living rooms of Ugandan households showed that concentrations in homes with solar lamps were about 40% of those in households using simple wick lamps. 17 Lacking have been studies of exposure of actual kerosene lamp users, and exposure changes from introducing kerosene lamp replacements.…”
mentioning
confidence: 99%